Bazı 7,8-dihidroksi-3-fenilkumarin makrohalkalı eter türevlerinin sentezi - Turan, Mükerrem (My University, 2000)
BİBLİYOGRAFYA SUMMARY 2H-1-Benzopryan-2-one (coumarins) which are deriatives of benzopryan, are widely distributed in plants and essential oils. They are used as fragrance components in parfumes, toothpastes and tobacco products. Moreover, coumarins are pharmacologically active and have been used in the treatment of diverse range of diseases, such as brucellosis, burns, rheumatic disease and even cancer. They occur in several families of higher plants in the free state or as glucodies. Because of the biological activity of these group of substances, many articals have been published according the synthesis and study of the physical activity of crown ether derivatives of coumarins. In this study, we synthesized different 2H-1-benzopran-2-one derivatives substituted in the third position with phenyl and p-metoxyphenyl groups, 7,8-dihydroxy-3-phenyl-2H-1-benzopryran-2-one and 7,8-dihydroxy-3-(p-methoxyphenyl)-2H-1-benzopryran-2-one. For the synthesis, we used two different method. 12-Crown-4,15-Crown-5 and 18-crown-6 derivatives of obtained coumarins were synthesized for the first time. In the synthesis of all coumarin-crown compounds, the same method has been followed. Accordingly; polyethylenglycolditosylate, 7,8-dihydroxy-3-phenyl-2H-1-benzopyran-2-one or 7,8-dihydroxy-3(p-methoxyphenyl)-2H-1-benzopryan-2-one were thoroughly dissolved in CH3CN/ K2CO3/ H2O systems. The mixture is heated and stirred mechanically under reflux for 35-40 hours between 70-75 0C. The solvent is removed. The purification is performed by using silicagel column choromatography. The proposed structure of the obtained coumarin-crown ethers were consistent with data provided by their 1H-NMR, IR and UV/ vis.

2H-1-benzopriran-2-on (kumarin) ve türevleri, bitki hücrelerinde sentezlenen ve bitki uçucu yağlarından elde edilen, parfümeride, dişmacunu ve tütün ürünlerinde maskeleyici katkı maddesi olarak kullanılan flavonoid bileşiklerinin bir alt grubunu oluştururlar. Ayrıca bu bileşikler bruselloz, yanık, romatizmal hastalıklar ve hatta kanser tedavisinde de kullanılabilen farmakolojik aktiviteye sahip doğal ürünlerdir. Bitkilerin çiçeklerinde serbest veya glukozitleri halinde bulunurlar. Biyolojik aktiviteleri nedeniyle araştırmacıların ilgisini çeken bu grup bileşiklerinin bazılarının taç eter türevleri sentezlenerek alkali ve toprak alkali metal katyonların tutulmasına benzopiran biriminin katkıları araştırıldı. Bu çalışma kapsamında farklı 2H-1-benzopriran-2-on iskeletinin 3. pozisyonunda fenil ve p-metoksifenil kökü bulunan 7,8-dihidroksi-3-fenil-2H-1-benzopiran-2-on ve 7,8-dihidroksi-3(p-metoksifenil)-2H-1-benzopiran-2-on türevleri sentetik olarak elde edildi. Sentezler için iki ayrı metod uygulandı. Elde edilen kumarin türevlerinin 12-taç-4,15-taç-5 ve 18-taç-6 türevleri ilk olarak sentezlendi. Taç eterlerin sentezi için polietilenglikolditosilat, 7,8-dihidroksikumarin veya 7,8-dihidroksi-3(p-metoksifenil)kumarin, CH3CN/ K2CO3/ H2O varlığında çözündü ve karışım geri soğutucu altında azot atmosferinde mekanik karıştırıcı ile karıştırılarak 70-75 oC arası 30-35 saat ısıtıldı.çözücü CH3CN destillenerek uzaklaştırıldıktan sonra karışım, silikajel kolon kromatografisinde saflaştırıldı. Yeni taç eterlerin yapıları IR, 1H-NMR ve UV/ vis spektrum değerleri ile karakterize edildi.
Keywords: Kimya, Organik-Eterler